تحسين مردود مقطر شمسي بسيط بدمجه بلاقط شمسي مصنوعان محليا: دراسة تجريبية - فاطمه باالقاسمي – طهراوي نسيبة (university of eloued جامعة الوادي, 2024)
ان تزايد مشكلة ندرة المياه الصالحة للشرب خاصة في المناطق النائية دفع الكثير من الباحثين للاهتمام بهذا الموضوع من أجل إيجاد حلول ناجعة له. من أهم هذه الحلول تقطير المياه المالحة وهو ما دفعنا لإستغلال تقنية التقطير الشمسي من أجل تحلية المياه، تم القيام بدراسة تجريبية من أجل تحسين أداء المقطر الشمسي البسيط وذلك بدمجه بلاقط حراري يساعد على رفع درجة حرارة الماء في حوض المقطر، حيث تم تركيب مبادل حراري (أنبوب نحاسي قطره 2.5سم) في قاع اللاقط وحوض المقطر المدمج معه مما يؤدي إلى زيادة درجة حرارة المياه في حوض المقطر، وهذا يزيد من كمية البخار الذي يتكثف ويتقاطر لاحقا وبالتالي تحسن إنتاجية المقطر. حيث تم تحسين مردود المقطر المدمج بلاقط بنسبة %22.4 مقارنة بنظيره الشاهد. The increasing problem of scarcity of potable water; especially in remote areas;has prompted many researchers to pay attention to this issue in order to find effective solutions. One of the most important of these solutions is the distillation of salt water, which is what prompted us to exploit solar distillation technology for water desalination. An experimental study was carried out in order to improve the performance of the simple solar distiller by integrating it whith a thermal collector that helps raise the temperature of the water in the still basin, where a exchanger was installed. (A copper tube with a diameter of 1.5 cm) at the bottom of the still and the distiller basin integrated with it, which leads to an increase in the water temperature in the distiller basin. This increases the amount of steam that condenses and drips later, thus improving the productivity of distilled water. The yield of the built-in distiller was improved by 22.4% compared to its reference counterpart.
م\كرة ماستر فيزياء
Keywords: لتقطير الشمسي، المقطر الشمسي البسيط ، اللاقط الشمسي، مبادل حراري ، ماء مقطر; Solar distillation; Simple solar still; Solar collector; Heat exchanger; distilled water.